2015
DOI: 10.1111/1365-2664.12488
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy and ecology of biocontrol and biomanipulation for managing invasive pest fish

Abstract: Summary Management of non‐native species aims to prevent biological invasions using actions including control and containment of the potential invader. Biocontrol and biomanipulation strategies are used frequently to reduce population sizes of non‐native species and reduce their ecological impacts and dispersal rates. Assessments of the efficacy of biocontrol and biomanipulation actions for managing non‐native pest fish, and the ecological mechanisms involved, were studied here using lentic populations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…60 by 30 cm crayfish traps with conical funnel entrance and fitted with 5 mm mesh netting). The depletion trapping was complemented by repeated, high density (116 kg ha −1 ) stocking of a native predatory fish, Eurasian perch ( Perca fluviatilis )—a biocontrol method that has been demonstrated to exert a top-down effect on P. parva abundance (Davies and Britton 2015; Verhelst et al 2016). Initial reports received by the authors indicated that by 2014, P. parva were no longer being captured; however, trapping data recently acquired from the venue’s owners revealed persistence of a very small number of P. parva , with the lowest capture densities occurring after predator releases (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…60 by 30 cm crayfish traps with conical funnel entrance and fitted with 5 mm mesh netting). The depletion trapping was complemented by repeated, high density (116 kg ha −1 ) stocking of a native predatory fish, Eurasian perch ( Perca fluviatilis )—a biocontrol method that has been demonstrated to exert a top-down effect on P. parva abundance (Davies and Britton 2015; Verhelst et al 2016). Initial reports received by the authors indicated that by 2014, P. parva were no longer being captured; however, trapping data recently acquired from the venue’s owners revealed persistence of a very small number of P. parva , with the lowest capture densities occurring after predator releases (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The removal of introduced populations is extremely difficult in most rivers and lakes, although some success has been achieved in England in smaller standing waters from which the invasive cyprinid topmouth gudgeon (Pseudorasbora parva) has been successfully removed by the controlled use of rotenone [59,60]. Nevertheless, the best management option is undoubtedly to prevent undesirable introductions from being made in the first place, and to this end all fish introductions to the UK are now subjected to sophisticated risk analyses [61].…”
Section: Management Management In and Around The Watermentioning
confidence: 99%
“…Pseudorasbora parva undergo boom and bust cycles in novel environments, most likely caused by a combination of biotic and abiotic factors, including temperature fluctuations and predation pressure (Britton et al, 2008;Britton et al, 2007). Trapping during low abundance or bust cycles may fail to yield any fish and result in false negatives (Davies & Britton, 2015). eDNA can be a more effective method for assessing presence/absence and could inform the success of eradication measures (Davison et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, one pond within the Millennium Coastal Park (Llanelli, South Wales) was reported to have P. parva, despite two previous eradication attempts in 2012 and 2013 (Brazier, 2015). The use of eDNA was recommended as a more sensitive and robust alternative to netting and trapping to test for the presence/absence of P. parva before any further eradication attempts (Davies & Britton, 2015).…”
Section: Introductionmentioning
confidence: 99%